2017
DOI: 10.1002/chem.201702566
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Synthesis of Ordered Mesoporous Carbon Nitrides with a High Nitrogen Content and Enhanced CO2 Capture Capacity

Abstract: Highly ordered mesoporous carbon nitrides (MCN) with 3D structure and a high nitrogen content are successfully prepared for the first time using "uncalcined" mesoporous silica template, KIT-6 and 3-amino-1,2,4-triazole as a single molecular carbon and nitrogen precursor. The prepared MCN with C and N stoichiometry of C N shows unique CN framework and exhibits the CO capture capacity of 5.63 mmol g at 273 K and 30 bar, which is higher than that of MCN with 2D structure and C N stoichiometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 36 publications
4
43
0
1
Order By: Relevance
“…It is interesting to note that the amount of nitrogen adsorbed in the monolayer region of the isotherm for Cr-MCN-10 which is used for the calculation of the specic surface area is much higher than those of other MCN samples discovered so far. 18,21,23,24,35,[39][40][41][42][43][44] Interestingly, the sample prepared with a low amount of AG registered the highest amount of nitrogen adsorption in the monolayer region than other samples prepared in this study. This indicates that the specic surface area of the samples can be controlled by varying the amount of AG precursor.…”
Section: Surface Area and Pore Size Analysis By Nitrogen Adsorptionmentioning
confidence: 51%
“…It is interesting to note that the amount of nitrogen adsorbed in the monolayer region of the isotherm for Cr-MCN-10 which is used for the calculation of the specic surface area is much higher than those of other MCN samples discovered so far. 18,21,23,24,35,[39][40][41][42][43][44] Interestingly, the sample prepared with a low amount of AG registered the highest amount of nitrogen adsorption in the monolayer region than other samples prepared in this study. This indicates that the specic surface area of the samples can be controlled by varying the amount of AG precursor.…”
Section: Surface Area and Pore Size Analysis By Nitrogen Adsorptionmentioning
confidence: 51%
“…On the other hand, non‐activated nitrogen containing carbon NEPB‐3U exhibits the CO 2 uptake of 4.3 and 2.8 mmol g −1 at 0 and 25 °C and 1 bar and 30 bar pressure, respectively. The highest CO 2 adsorption capacity of 14.1 mmol g −1 at 0 °C and 30 bar was recorded by NEPB‐3UK, which is three times higher than that of mesoporous carbon nitride materials with C 3 N 4 stoichiometry and two‐dimensional porous structure (4.67 mmol g −1 at 0 °C and 30 bar) . From Table it is evident that the CO 2 uptake performance of these materials is strongly dependent on the specific BET surface area of the materials, although the presence of basic functionalities further augments the CO 2 adsorption.…”
Section: Resultsmentioning
confidence: 92%
“…When tested under conditions that mimic pre‐and post‐combustion processes, the synthesized activated biocarbons demonstrated a high value of CO 2 uptake at 4.8 mmol g −1 and 14.1 mmol g −1 at 0 °C under a pressure variation of 1 bar and 30 bar, respectively. For better understanding, we compared the CO 2 adsorption capacities and isosteric heat of adsorptions of NEPB‐3UK with other N‐functionalized adsorbent materials including amines‐modified porous silica and zeolite, and mesoporous carbon nitrides (Table S3) ,. The high CO 2 adsorption capacity of these materials is attributed to the presence of high microporous surface area and high nitrogen content in the form of pyridinic‐N and pyrrolic‐N species in the framework of porous structure.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the pore structure and N‐doping of the N‐HPC‐800 also influenced the high‐pressure CO 2 adsorption capacity. As demonstrated in previous reports, super‐micropores or small mesopores (below 2–3 nm) govern the sorption behavior at a high pressure, and basic functional groups by N‐doping are favorable for the adsorption of acidic CO 2 molecules . We compared the performances of our N‐HPC‐800 to representative porous carbon materials as CO 2 high‐pressure solid adsorbents.…”
Section: Resultsmentioning
confidence: 99%